2020
DOI: 10.26559/mersinsbd.648783
|View full text |Cite
|
Sign up to set email alerts
|

Determination of oral-dental health status in children with heart disease and level of awareness of infective endocarditis in their parents

Abstract: Amaç: Bu çalışmada, doğuştan kalp hastalığı olan çocukların ağız-diş sağlığı durumlarının sağlıklı kontrollerle karşılaştırılması ve hasta çocukların ebeveynlerinin infektif endokardit (İE) bilgi düzeyinin ve İE'den korunma yolları farkındalıklarının değerlendirilmesi amaçlanmıştır. Yöntem: Prospektif, kontrollü bir çalışma olarak planlanan bu kohorta doğuştan kalp hastalığı ile izlenen, yaşları 5-18 yaş arası 71 hasta ve 70 kontrol grubu olmak üzere 141 çocuk dahil edildi. Ebeveynlerin hastalık ve İE ile ilgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
(14 reference statements)
0
0
1
Order By: Relevance
“…In a study that assessed the oral health of children with CHD in western Norway, Sivertsen et al [2] remarked that 1/3 of the children suffering from CHD had oral conditions that might pose a risk for systemic disorders. Similarly, in a study conducted in Türkiye, evaluating the knowledge and awareness of the CHD-impacted children's parents on the relationship between oral and dental health and IE, Yilmaz et al revealed that 35.4% of the parents did not recognize this correlation [32]. Although not assessed in our study, higher mean values of dental plaque and presence of gingivitis might have been associated with poor parental awareness of the IE and CHD relationship.…”
Section: Discussioncontrasting
confidence: 51%
“…In a study that assessed the oral health of children with CHD in western Norway, Sivertsen et al [2] remarked that 1/3 of the children suffering from CHD had oral conditions that might pose a risk for systemic disorders. Similarly, in a study conducted in Türkiye, evaluating the knowledge and awareness of the CHD-impacted children's parents on the relationship between oral and dental health and IE, Yilmaz et al revealed that 35.4% of the parents did not recognize this correlation [32]. Although not assessed in our study, higher mean values of dental plaque and presence of gingivitis might have been associated with poor parental awareness of the IE and CHD relationship.…”
Section: Discussioncontrasting
confidence: 51%